Telling a Good Story: Meeting with Bill Knight and David Lindsell, Chairman and Deputy Chairman of the Financial Reporting Review Panel - Bender, Ruth (Cranfield University, 2009)
Prepared for the Audit Committee Chair Forum, published by Ernst & Young, CBI and Cranfield School of Management. This paper reflects the discussions at a meeting of the Audit Committee Chair Forum(ACCF) held on 8th June 2009, which was addressed by Mr Bill Knight and Mr DavidLindsell, respectively the Chairman and Deputy Chairman of the Financial ReportingReview Panel ("FRRP" or "the Panel"). The meeting discussed financial reporting in the UK and the work of the Panel.